Analisa proses produksi part number D574-50081-201 menggunakan mesin milling CNC di PT DI - Eko Budiyanto; Lukito Dwi Yuono; Fatku Rohman (TURBO [Tulisan Riset Berbasis Online], 2020)
The world of manufacturing technology is currently developing rapidly. Computerization carried out on manufacturing equipment makes it very easy for an industry, especially industries with a large production scale or mass production with a high number of orders in a short time. Manufacturing technology for machine tools usually uses a CNC (Computer Numeric Control) machine. Where the operation of this machine uses a program controlled by a computer and the programmer. This machine can produce products with high accuracy, even for very complicated manufacturing work. Product errors due to operator negligence can be reduced, as contact between the operator and the machine is minimal. However, if there is an error in the material or improper feed, the operator tends not to know because everything has been executed with the program that has been made. Observations were made at the 3 axis prismatic machine section, PT. Dirgantara Indonesia (DI). The milling machine used was the QUASER MV 185 type machine. Part material used in this study was Aluminum alloy 7010. The results of observations and calculations obtained that the average machining efficiency was 13%. Keywords: CNC, production process, efficiency.